FACTORS INFLUENCING THE INCIDENCE OF ANEMIA IN ADOLESCENT GIRLS AT HADI HUSADA HOSPITAL - Ika Lestari; Mallisa Juni Aisyah Hasibuan; Nur ‘Aini Dalimunthe (Cattleya Darmaya Fortuna, 2025)
Anemia is a condition with lower than normal hemoglobin and erythrocyte levels (Masrizal, 2007). Factors influencing the incidence of anemia in adolescent girls. This type of research is an analytical survey using a cross-sectional design. The population in this study were all pregnant women at Hadi Husada Hospital. The sampling technique used was total sampling of 33 people. The data collection tool was a questionnaire. The results of the study showed that the statistical test results obtained a p value = 0.001 or an α value <0.05 which can be concluded that there is a significant influence between female students' knowledge on the incidence of anemia, the statistical test obtained a p value = 0.003 or an α value <0.05 which can be concluded that there is a significant influence between female students' activities on the incidence of anemia, the statistical test obtained a p value = 0.000 or an α value <0.05 which canbe concluded that there is a significant influence between the length of menstruation on the incidence of anemia, the statistical test obtained a p value = 0.000 or an α value <0.05 which can be concluded that there is a significant influence between nutritional status on the incidence of anemia. It is hoped that young women should be able to know about health, especially about nutritional status on the incidence of anemia and it is hoped that further researchers will conduct research with more samples and different designs.